Bioresorbable Metals for Biomedical Applications: From Mechanical Components to Electronic Devices. Issue 17 (15th February 2021) - Ryu, Hanjun; Seo, Min‐Ho; Rogers, John A.
Abstract: Bioresorbable metals and metal alloys are of growing interest for myriad uses in temporary biomedical implants. Examples range from structural elements as stents, screws, and scaffolds to electronic components as sensors, electrical stimulators, and programmable fluidics. The associated physical forms span mechanically machined bulk parts to lithographically patterned conductive traces, across a diversity of metals and alloys based on magnesium, zinc, iron, tungsten, and others. The result is a rich set of opportunities in healthcare materials science and engineering. This review article summarizes recent advances in this area, starting with an historical perspective followed by a discussion of materials options, considerations in biocompatibility, and device applications. Highlights are in system level bioresorbable electronic platforms that support functions as diagnostics and therapeutics in the context of specific, temporary clinical needs. A concluding section highlights challenges and emerging research directions. Abstract : Bioresorbable metals and metal alloys are of great interest as temporary biomedical implants for scaffolds, stents, screws, sensors, and electrical stimulators. Herein, bioresorbable metals and applications related to these areas are summarized, including the chemistry of bioresorption and issues in biocompatibilityfor such materials in bulk form, in thin films and in composites, with highlights of their emerging use in transient electronics.